The current density order based on the Ginzburg-Landau description - Bousnane, Z.; Merabtine, N.; Benslama, M.; Bousaad, F. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2007)
The goal of this survey is to deduce the grandeurs, or the set of grandeurs,
from which is derived simultaneously as a linear combination of densities of states,
current density matrix and the reduced entropy, according to the general fact that the
logarithm of the distribution is additive first integral. In this perspective, we introduce the
notations, which gives to the logarithm of the distribution as the
quaternionic picture of the operatorial transcriptions, this must follow the behaviour of a
canonical distribution through the interval of the transitions. It seems that the
nonreproducibility is caused essentially by the fact of absolute separability of dimensions
between the observed and observer. The reduced entropy will suggest the inner
displaying of observer, the invariance of unsymmetric order parameter products will be
an expression of reproducibility. We must have a displaying of such products over inner
dimensions, allowing to translate a limit of the displaying of stationary levels of
macroscopic bodies over inner distances. Iˆ is the parity operator and will act under
respect or violation of products as uncertainties, Jˆ is representing measurement process
decomposing layers, sublayers and orbitals according to the thresholds logics answering
how cold will be felt to transgress the conventional univoc filling rules, Kˆ represents
measurement process realising the centesimal entropy depth penetration. The
introduction of such notations will be justified by the fact that the ρ -distribution,
introduced as an unsymmetric product of order parameters, is defined per pavement –
pavement as defined by J.H. Poincaré.